ColloVoc: technology-enhanced listening processing approach - Liew, Madeline Szu Hwa; Mistar, Izyani; Abd Aziz, Rohaizad; A. Hamid, Siti Musalmah (2025)
Colloquial language presents challenges for students in listening comprehension, particularly when it includes implied meanings, idiomatic expressions, and informal conversational phrases. However, mastering it equips learners for real-world interactions and makes entertainment more enjoyable. Therefore, an innovative Teaching and Learning (T&L) strategy namely ColloVoc has been created by the AIMS group using Top-Down/Bottom-Up (TD-BU) processing model for learning colloquial language interactively. This innovation integrates digital instructional strategies by incorporating YouTube, YouGlish and AI tools to strengthen students' listening comprehension and ability to decode informal language structures in spoken English. Through two cycles of iterative lesson planning, observation, and refinement, 20 students from the A1P3 practicum engaged in enhanced lesson activities and instructional materials designed to achieve learning objectives. This T&L innovation explores how the TD-BU Model, combined with digital learning tools, can improve inferential listening skills. The findings highlight the significance of structured interventions and technology-driven language tools in bridging academic instruction with real-world conversational English. As part of the ongoing educational reformation aimed at fostering a digital generation, this innovative strategy offers valuable insights into the pedagogical adjustments needed for integrating technology into language learning, equipping students to confidently engage in authentic conversations.